2022
DOI: 10.1158/1055-9965.epi-22-0069
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ancestry-Specific 6q25 Variants and Breast Cancer Subtypes in Peruvian Women

Abstract: Background: Breast cancer incidence in the United States is lower in Hispanic/Latina (H/L) compared with African American/Black or Non-Hispanic White women. An Indigenous American breast cancer–protective germline variant (rs140068132) has been reported near the estrogen receptor 1 gene. This study tests the association of rs140068132 and other polymorphisms in the 6q25 region with subtype-specific breast cancer risk in H/Ls of high Indigenous American ancestry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, Zavala et al explored the correlation between rs140068132 and other polymorphisms in the 6q25 region, examining subtype-specific breast cancer risk in Latin Americans with high Native American (NA) ancestry. Their findings revealed that rs140068132 is associated to a decreased risk of breast cancer in Peruvian adults, providing greater defense against cases with negative hormone receptor (HR−) and HER2+ [ 37 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…Furthermore, Zavala et al explored the correlation between rs140068132 and other polymorphisms in the 6q25 region, examining subtype-specific breast cancer risk in Latin Americans with high Native American (NA) ancestry. Their findings revealed that rs140068132 is associated to a decreased risk of breast cancer in Peruvian adults, providing greater defense against cases with negative hormone receptor (HR−) and HER2+ [ 37 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally 27–40 . Ancestry‐associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%
“…Oncologic anthropology is also relevant in studying the breast cancer burden of Latina/Hispanic women internationally. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Ancestry-associated variants have been identified that predict risk from specific breast cancer phenotypes among Latina women in the United States, in Central America, and in South America. These studies have also found that among admixed Latina women, the extent of European ancestry increases the risk of breast cancer, whereas extent of Indigenous American ancestry decreases the risk of breast cancer.…”
Section: Oncologic Anthropology: Influence Of Germline Genetic Ancest...mentioning
confidence: 99%